The Effects of The Infusion Cortex of Langsat (Lansium domesticum L.) to Decrease Blood Glucose Levels on The Diabetic Rats Inducted with Alloxan - Lukman La Bassy; Risman Tunny; Aulia Deby Pelu (Humanistic Network for Science and Technology (HNST), 2018)
Background Blood glucose levels are a critical factor for maintaining the bodywork. Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels due to abnormalities of insulin secretion and insulin work or both.One of Indonesia's native plants that are suspected of potentially as an antidiabetic is Langsat (Lansium domesticum L.). Empirically, this plant has been used by Maluku community as an antimalarial drug, but there was no scientific report on the utilization of this plant extract as an antihiperglicemia drug.Objective This research was conducted to determine the effect of the infusion cortex of langsat (Lansium domesticum L.) to decrease blood glucose in diabetic rat models.Method Twenty five of Wistar malerats aged 6-8 weeks, weighing 180-200 grams were used in this study. Subjects were induced with Alloxan 110 mg/kgbw. Subjects were grouped into five groups, namely; 1) 10 g/kgbw of the infusion cortex of langsat group, 2) 20 g /kgbw of the infusion cortex of langsat group, and 3) 30 g/kgbw of the infusion cortex of langsat group 4) diabetes group, and 5) control group. The Infusion was given for ± 21 days and blood glucose examination was conducted before and after this tretment.Results There was a significant decrease in blood glucose levels in the 10 g/kgbw, 20 g/kgbw, 30 g/kgbw of the infusion cortex of langsat groups (p<0.05). Best effects offered by 30g/kgbw dose. Conclusion: Infusion cortex of langsat (Lansium domesticum L.) to decrease blood glucose levels in hyperglycemic conditions rats induced by Alloxan. The most effective dose to lower blood glucose levels was 30 g/kgbw. Keywords: Diabetic, Blood glucose, Cortex of langsat (Lansium domesticum L.)